2018
DOI: 10.4039/tce.2017.63
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal and synergistic activity of two monoterpenes against diamondback moth (Lepidoptera: Plutellidae)

Abstract: We examined the insecticidal activity of linalool and thymol, against diamondback moth,Plutella xylostella(Linnaeus) (Lepidoptera: Plutellidae), and whether they would synergise the activity of spinosad against this pest. Both linalool and thymol were toxic to diamondback moth larvae by topical and oral exposure, but orders of magnitude less so than spinosad. We found that low concentrations of linalool weakly synergised spinosad, increasing its toxicity more than twofold. An interaction between spinosad, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
2
1
Order By: Relevance
“…Therefore, similar synergistic effects can explain the lower toxicity of individual compounds with respect to O. vulgare leaves. Despite the known effects of thymol as an insecticide [ 49 , 50 , 51 ], no significant effects were observed in our study, probably because of the very low amount of thymol produced by the O. vulgare chemotype used in this study.…”
Section: Discussioncontrasting
confidence: 76%
“…Therefore, similar synergistic effects can explain the lower toxicity of individual compounds with respect to O. vulgare leaves. Despite the known effects of thymol as an insecticide [ 49 , 50 , 51 ], no significant effects were observed in our study, probably because of the very low amount of thymol produced by the O. vulgare chemotype used in this study.…”
Section: Discussioncontrasting
confidence: 76%
“…It is worth noting that the only structural difference between these two compounds is the position of the hydroxyl group on the benzene ring relative to the larger aliphatic chain and may be related to this difference in activity [60]. However, it is important to note that the efficacy of thymol is well reported for several insect species, such as Anopheles stephensi (Liston, 1901) (Diptera: Culicidae) [61], S. zeamais [62], and Plutella xylostella (Linnaeus, 1758) (Lepidoptera: Plutellidae) [19].…”
Section: Discussionmentioning
confidence: 99%
“…Natural products are generally efficient, low cost, and less harmful than synthetic products to nontarget organisms, and because of their biodegradability, they are ecologically appropriate [17,18]. Both commercially available formulations and rudimentary essential oils have shown promise in pest control for crops [19]. Recent research has shown a growing interest in the bioactive effects of essential oils and their derivatives on insects [20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%